A Problem of Long - Term Digital Preservation: Difference in Humanities and Natural Sciences - Macevičiūtė, Elena (Bibliotheca Lituana, 2014)
The article deals with the requirements and needs for long-term digital preservation in different areas of scholarly work. The concept of long-term digital preservation is introduced by comparing it to digitization and archiving concepts and defined with the emphasis on dynamic activity within a certain time line. The structure of digital preservation is presented with regard to the elements of the activity as understood in Activity Theory. The life-cycle of digitization processes forms the basis of the main processing of preserved data in preservation archival system.The author draws on the differences between humanities and social sciences on one hand and natural and technological science on the other. The empirical data characterizing the needs for digital preservation within different areas of scholarship are presented and show the difference in approaches to long-term digital preservation, as well as differences in selecting the items and implementing the projects of digital preservation. Institutions and organizations can also develop different understanding of preservation requirements for digital documents and other objects.The final part of the paper is devoted to some general problems pertaining to the longterm digital preservation with the emphasis of the responsibility for the whole process of safe-guarding the cultural and scholarly heritage for the re-use of the posterior generations. It is suggested that the longevity of the libraries in comparison with much shorter life-span of private companies strengthens the claim of memory institutions to playing the central role in the long-term digital preservation.
Keywords: none